PERAN PEMERINTAH DAERAH PROVINSI RIAU MENGATASI DAMPAK KEBAKARAN HUTAN DAN LAHAN TAHUN 2015 DAN 2019 - Riski Nanda Situngkir; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Burning peatlands is the biggest cause of forest and land fires, because peat forests have high degradation, so forest and land fires often occur in peatland areas. It was recorded that in the 2015-2019 range 77.3% of forest and land fires occurred in Riau Province is located on peatlands. The purpose of this study is to describe the role of the government and what efforts are being made to anticipate forest fires that occur with one of the efforts being made to carry out prevention through institutions is the formation of Manggala Agni. Manggala Agni is an Indonesian forest fire control brigade formed by the Ministry of Forestry in 2003, to carry out forest fire control which includes prevention, suppression and post-fire management. In Riau Province there are 4 (four) Manggala Agni spread across Pekanbaru City, Siak Regency, Dumai City and Indragiri Hulu Regency (Rengat District to be exact) with 14 team strengths and 210 team members. The results of this research are first, the government realizes that the role of the Government itself is important and very much needed in preventing the handling of Forest and Land Fires, secondly actions and cooperation are carried out to realize a way to facilitate the handling of forest fires in Riau Province. Keyword : Peatlands, Role of Government and Cooperation